Recent Trend in Electromagnetic Radiation and Compliance Assessments for 5G Communication - Nor Adibah Ibrahim; Tharek Abd. Rahman; Olakunle Elijah (Institute of Advanced Engineering and Science, 2017)
The deployment of the 5G networks will feature high proliferation of radio base station (RBS) in order to meet the increasing demand for bandwidth and also to provide wider coverage that will support more mobile users and the internet-of-things (IoT). The radio frequency (RF) waves from the large-scale deployment of the RBS and mobile devices will raise concerns on the level of electromagnetic (EM) radiation exposure to the public. Hence, in this paper, we provide an overview of the exposure limits, discuss some of the effects of the EM emission, reduction techniques and compliance assessment for the 5G communication systems. We discuss the open issues and give future directions.